Familial Russell–Silver Syndrome like Phenotype in the PCNA Domain of the CDKN1C Gene, a Further Case - A. H. Sabir; G. Ryan; Z. Mohammed; J. Kirk; N. Kiely; M. Thyagarajan; T. Cole (Case Reports in Genetics)
We present two half siblings with significant short stature who proved a diagnostic challenge for several years. Radiological findings included subtle epiphyseal changes. The diagnosis was made through whole genome sequencing via the 100,000 genome project. A maternally inherited pathogenic heterozygous CDKN1C variant was found in the PCNA (proliferating cell nuclear antigen) domain. Mutations of the PCNA domain of the CDKN1C gene are known to be associated with IMAGe syndrome thus with adrenal disease, although neither affected patient in our case had evidence of adrenal dysfunction. This report supports the previously reported findings of Russell–Silver syndrome (RSS) like phenotype caused by this unusual mechanism (CDKN1C mutations in the PCNA domain), highlights subtle radiological features not described previously and the phenotypic variability between two affected siblings. Additionally it reminds clinicians of the importance of considering associated adrenal disease/diabetes mellitus for variants within the PCNA domain. Finally it confirms RSS-like disorders should be considered in patients who have epiphyseal or metaphyseal changes and short stature, since CDKN1C PCNA domain mutations can result in this phenotype.